Legal Protection of Hawker Children Working in MSMEs: Perlindungan Hukum bagi Anak-Anak Pedagang Kaki Lima yang Bekerja di Usaha Mikro, Kecil, dan Menengah - Nabilla Angel Azzaroh; Sri Budi Purwaningsih (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Child labor in Indonesia remains a complex social issue, especially within Micro, Small, and Medium Enterprises (MSMEs), where informal employment often overlooks children’s rights. Specific Background: Many hawker children in Sidoarjo Regency work without contracts, fair wages, or safety standards, violating labor law provisions. Knowledge Gap: Previous studies have discussed child labor broadly but have not specifically examined the enforcement of hawker children’s rights within MSME contexts through a legal lens. Aim: This study aims to analyze the legal protection and enforcement of hawker children’s rights under Indonesian labor law. Results: Findings show that child workers in MSMEs experience excessive working hours, sub-minimum wages, and lack of contracts or occupational safety measures, primarily due to low legal awareness among MSME owners and weak supervision. Novelty: The study uses a conceptual and statutory approach by linking MSME regulations with labor law principles. Implications: The research suggests the need for inclusive labor policies, consistent law enforcement, legal education for entrepreneurs, and empowerment programs ensuring children’s rights to education and welfare. Highlights:• Hawker children’s legal status in MSME labor relations• Weak enforcement of child labor laws in informal sectors• Policy recommendations for inclusive labor protection Keywords: Child Labor, MSMEs, Legal Protection, Informal Sector, Indonesia